Gardening the interior: Odo Strewe inside the 1980s - Francis, Kerry (Architectural History Aotearoa, 2022)
Odo Strewe arrived in New Zealand in 1938, a refugee from Nazi Germany. After release from internment on Matiu (Somes Island) as an Enemy Alien during World War Two, he married and moved to Auckland where he started a landscape design and construction business. Strewe had explored the idea of plants inside buildings in the very first house that he had made for his family in Glen Eden, Auckland in 1949. An Australian journalist writing about the house described the interior "with tropical paw paws almost coming indoors to join forces with the banana that is really growing and fruiting, right inside the house." Strewe continued to advocate for this disciplinary contest in subsequent years by writing about indoor gardening in New Zealand Modern Homes and Gardens and designing gardens that challenged the boundaries between landscape and the interior. This paper will explore the design strategies of two of Strewe’s interior gardens in the 1960s as he developed this aspect of his landscape design practice.